2020
DOI: 10.1177/1010428320925237
|View full text |Cite
|
Sign up to set email alerts
|

KCNB1 gene polymorphisms and related indel as predictor biomarkers of treatment response for colorectal cancer – toward a personalized medicine

Abstract: The KCNB1 gene variants were differentially associated with cancers. However, their association with colorectal cancer has not yet been explored. We investigated the contribution of the KCNB1 gene variants rs3331, rs1051295, and indel (insertion/deletion) rs11468831 Polymorphism as predictors of the treatment response in colorectal cancer patients. A retrospective study, which involved 291 Tunisian colorectal cancer patients (aged 60.0 ± 13.1 years), who were stratified into responder and non-responder groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…OR10Q1 encodes for an olfactory receptor that has so far not been studied [ 117 ]. KCNB1 is a potassium voltage-gated channel that is highly expressed in the brain and has been identified as a biomarker for colorectal cancer and associated with a favorable prognosis in glioma patients [ 114 , 118 , 119 ]. Specifically, it was shown that KCNB1 regulates autophagy through the ERK signaling pathway and acts as a tumor suppressor [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…OR10Q1 encodes for an olfactory receptor that has so far not been studied [ 117 ]. KCNB1 is a potassium voltage-gated channel that is highly expressed in the brain and has been identified as a biomarker for colorectal cancer and associated with a favorable prognosis in glioma patients [ 114 , 118 , 119 ]. Specifically, it was shown that KCNB1 regulates autophagy through the ERK signaling pathway and acts as a tumor suppressor [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…The elevation in serum levels of the identified mediators in patients with CRC patients underscores the state of inflammation accompanying CRC [ 18 , 19 ]. It was shown that heightened IFN-γ levels are generally tumor-suppressive [ 8 , 19 ], and that deficiency of IFN-γ or its receptor-promoted colorectal carcinogenesis [ 20 ], thus prompting the conclusion of a key role for IFN-γ in patient survival [ 3 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The surprising variability of Kv2.1 function within the microenvironment highlights the possible if not likely importance of such channels in CRC and suggests additional studies to discover Kv2.1 function that may be modified adversely with Western influenced lifestyles such as increased fat and meat consumption. In addition, our recent results showed that KCNB1 polymorphisms were associated with Tumor-Node-Metastasis (TNM) progression and treatment response and suggests that such polymorphisms as biomarkers of CRC outcomes, before and during chemotherapy process [ 17 ]. The accumulated body of evidence of the importance and functional contribution of Kv2.1 in cancer suggested the importance of testing variants’ of KCNB1 (the Kv2.1 coding gene) association with CRC, CC and RC.…”
Section: Discussionmentioning
confidence: 99%
“…Consideration of such protein families’ role in apoptosis regulation suggests that potassium channels are regulators of cancer cell death and may lead to promising therapeutic targets. In particular, a recent study by this group provides evidence about the association of KCNB1 polymorphisms (rs3331, rs1051295 and rs11468831) and treatment response and may help predict if not contribute to anticancer treatment response, a part of a new approach for monitoring the disease kinetics during the chemotherapy process [ 17 ].…”
Section: Introductionmentioning
confidence: 99%